Controversy of Early Marriage Between Religious Doctrine and Customs in Minority Areas in Indonesia - Huzaimah, Arne; Abdillah, Muhammad; Tamudin, M.; Holijah, Holijah; Rohmawati, Rohmawati; Sari, Intan Permata (Jurnal Ilmiah Al-Syir'ah, 2024)
The early marriage controversy is a significant issue that affects people's views regarding marriage within the framework of Islamic religious doctrine and customs in Indonesia. This article examines how Islamic law adapts in response to socio-cultural changes, especially in regions with Muslim minority populations, which have mixed interpretations of the age of marriage. This study uses a qualitative descriptive approach with data collection through news and literature relevant to the keyword "Early marriage controversy in Indonesia." The analysis was carried out inductively to identify the forms, factors, and impacts of early marriage controversies on the lives of young couples, both from the perspective of health, quality of life, and religious and cultural norms. The results of the study show that this controversy reflects the challenges of integrating Islamic religious doctrine with local customary values, creating both positive and negative consequences for couples who marry young. In the context of Muslim minorities, this article recommends a flexible and responsive approach to Islamic law to socio-cultural dynamics, in order to achieve a balance between religious norms and the social needs of diverse communities.